The role of beta-blockers in the treatment of hypertension in 2018 ESC/ESH guidelines - A. O. Konradi; L. G. Ratova; I. V. Emelyanov; A. O. Nedoshivin (Российский кардиологический журнал)
Arterial hypertension (AH) is the most common noninfectious disease in the world and in Russia, associated with high cardiovascular morbidity and mortality. In August 2018, new guidelines for the diagnosis and treatment of patients with arterial hypertension were presented at the European Congress of Cardiology. The article discusses the role of the sympathetic nervous system in the pathogenesis of hypertension and the current importance of betablockers in the treatment of hypertension.